Genomic aberrations in cervical adenocarcinomas in Hong Kong Chinese women. Issue 4 (13th February 2015) - Chung, Tony K.H.; Van Hummelen, Paul; Chan, Paul K.S.; Cheung, Tak Hong; Yim, So Fan; Yu, Mei Y.; Ducar, Matthew D.; Thorner, Aaron R.; MacConaill, Laura E.; Doran, Graeme; Pedamallu, Chandra Sekhar; Ojesina, Akinyemi I.; et al.
<x xml:space="preserve">Abstract</x> Although the rates of cervical squamous cell carcinoma have been declining, the rates of cervical adenocarcinoma are increasing in some countries. Outcomes for advanced cervical adenocarcinoma remain poor. Precision mapping of genetic alterations in cervical adenocarcinoma may enable better selection of therapies and deliver improved outcomes when combined with new sequencing diagnostics. We present whole‐exome sequencing results from 15 cervical adenocarcinomas and paired normal samples from Hong Kong Chinese women. These data revealed a heterogeneous mutation spectrum and identified several frequently altered genes including FAT1, ARID1A, ERBB2 and PIK3CA. Exome sequencing identified human papillomavirus (HPV) sequences in 13 tumors in which the HPV genome might have integrated into and hence disrupted the functions of certain exons, raising the possibility that HPV integration can alter pathways other than p53 and pRb. Together, these provisionary data suggest the potential for individualized therapies for cervical adenocarcinoma based on genomic information.